Si voglia risolvere la seguente equazione:
\( 2cos^2(x)-3cosx+1=2sin^2(x)\)
Soluzione
Siccome:
\( cos^2(x)+sin^2(x)=1\)
Si ha che:
\(sin^2(x)=1-cos^2(x)\)
E quindi la \( 2cos^2(x)-3cosx+1=2sin^2(x)\)diventa:
\( 2cos^2(x)-3cosx+1=2[1-cos^2(x)]\)
E ancora:
\(2cos^2(x)-3cosx+1=2-2cos^2(x) \rightarrow\)
\( 4cos^2(x)-3cosx-1=0 \rightarrow\)
Ponendo:
\( t=cosx\)
Si ha:
\( 4t^2-3t-1=0\)
Da cui si può calcolare:
\( t_{1,2} = \frac{-(-3) \pm \sqrt{(-3)^2-4(4)(-1)}}{2 \cdot 4} \rightarrow\)
\(t_{1,2} = \frac{3 \pm \sqrt{25}}{8} \rightarrow\)
E quindi:
\( t_{1} = -\frac{1}{4}\)
e \( t_{2} = 1\)
Siccome poi:
\( t=cosx\)
Si ha che:
\( x_{1} = \pm arccos(-\frac{1}{4}) + 2k \pi \wedge x_{2} = 2k \pi\) con \(x k \in \mathbb{Z}\)